SPINEL-GARNET LHERZOLITE TRANSITION IN THE SYSTEM CAO-MGO-AL2O3-SIO2 REVISITED: AN IN SITU X-RAY STUDY - Walter M.; Katsura T.; Kubo A.; Shinmei T.; Nishikawa O.; Ito E.; Lesher C.; Funakoshi K. (My University, 2002)
Large discrepancies are reported for the near-solidus, pressure-temperature location of the spinel to garnet lherzolite univariant curve in the system CaO-MgO-Al2O3-SiO2 (CMAS). Experimental data obtained previously from the piston-cylinder apparatus indicate interlaboratory pressure differences of up to 30% relative. To investigate this disparity-and because this reaction is pivotal for understanding upper mantle petrology-the phase boundary was located by means of an independent method. The reaction was studied via in situ X-ray diffraction techniques in a 6-8 type multianvil press. Pressure is determined by using MgO as an internal standard and is calculated from measured unit cell volume by using a newly developed high-temperature equation of state for MgO. Combinations of real-time and quenched-sample observations are used to bracket the phase transition. The transition between 1350 and 1500°C was reversed, and the reaction was further constrained from 1207 to 1545°C. Within this temperature range, the transition has an average dT/dP slope of ~40 +/- 10°C/kbar, consistent with several previous piston-cylinder studies. Extrapolation of our curve to 1575°C, an established temperature of the P-T invariant point, yields a pressure of 25.1 +/- 1.2 kbar. We also obtained a real-time reversal of the quartz-coesite transition at 30.5 +/- 2.3 kbar at 1357°C, which is about 2 to 4 kbar lower in pressure than previously determined in the piston-cylinder apparatus.